PERENCANAAN OBJEK WISATA ALAM DAN TANTANGAN DALAM PENYEDIAAN INFRASTRUKTUR TRANSPORTASI - Eka Putra, Kaspan; Zainuddin (Jurnal Koridor, 2017)
Development of the tourist attractions are the leading sectors in encouraging the growth of development in the region. Each area that has a potential tourist attraction is planed and developed as a main destination that will be offered to tourists. This study analyzes the development planning of natural attractions and challenges in providing transport infrastructure. This study was conducted in Simalungun using primary data through observation of objects and explorative analyzes. The results showed there is a natural tourist attraction waterfall Tinggi Raja with huge potential, but constrained by the availability of transportation infrastructure that is very damaged. Simalungun government has not planned construction of the necessary infrastructure in the development of attractions.